THE STRATEGIES USED BY ENGLISH TEACHERS OF SMK TARUNA PEKANBARU IN TEACHING ENGLISH - Dwi Asmia Putri; Supriusman; Novitri (International Journal of Educational Best Practices, 2026)
English plays a central role in global communication and education, making effective teaching strategies essential to support students’ language development. However, teaching English in non-English-speaking contexts, such as Indonesia, remains challenging, particularly in vocational schools, where academic subjects often receive less emphasis than technical training. This study investigates the strategies employed by English teachers of SMK Taruna Pekanbaru in teaching English and explores the challenges their encountered in the classroom. Using a descriptive qualitative design, data were collected through classroom observations and interviews involving three English teachers. The findings revealed that Teacher 1 applied a combination of expository and inquiry-based strategies, whereas Teachers 2 and 3 consistently implemented inquiry learning approaches. While inquiry strategies encouraged critical thinking, collaboration, and active participation, the expository method was useful for providing clarity, especially for students with lower academic ability. Despite these efforts, teachers faced obstacles such as limited instructional time, low student motivation, and inadequate learning facilities. The results highlighted that although teachers adapted strategies to meet classroom needs, structural constraints within the semi-military vocational school environment restrict the effectiveness of English instruction. This study contributes to the growing literature on English language teaching strategies in vocational contexts and offers insights for educators, policymakers, and future researchers seeking to improve language learning outcomes in similar educational settings.